The identification of differentially expressed genes in male and female gametophytes of simple thalloid liverwort Pellia endiviifolia sp. B using an RNA-seq approach - Sierocka, Izabela; Alaba, Sylwia; Jarmolowski, Artur; Karlowski, Wojciech M.; Szweykowska-Kulinska, Zofia (Planta, 2020)
Main conclusion This study shows differences in gene expression between male and female gametophytes of the simple thalloid liverwort with a distinction between the vegetative and reproductive phases of growth. Pellia endiviifolia is a simple thalloid liverwort that, together with hornworts and mosses, represents the oldest living land plants. The limited taxon sampling for genomic and functional studies hampers our understanding of processes governing evolution of these plants. RNA sequencing represents an attractive way to elucidate the molecular mechanisms of non-model species development. In the present study, RNA-seq was used to profile the differences in gene expression between P. endiviifolia male and female gametophytes, with a distinction between the vegetative and reproductive phases of growth. By comparison of the gene expression profiles from individuals producing sex organs with the remaining thalli types, we have determined a set of genes whose expression might be important for the development of P. endiviifolia reproductive organs. The selected differentially expressed genes (DEGs) were categorized into five main pathways: metabolism, genetic information processing, environmental information processing, cellular processes, and organismal systems. A comparison of the obtained data with the Marchantia polymorpha transcriptome resulted in the identification of genes exhibiting a similar expression pattern during the reproductive phase of growth between members of the two distinct liverwort classes. The common expression profile of  87 selected genes suggests a common mechanism governing sex organ development in both liverwort species. The obtained RNA-seq results were confirmed by RT-qPCR for the DEGs with the highest differences in expression level. Five Pellia -female-specific and two Pellia -male-specific DEGs showed enriched expression in archegonia and antheridia, respectively. The identified genes are promising candidates for functional studies of their involvement in liverwort sexual reproduction.